COINOCULAÇÃO COM AZOSPIRILLUM BRASILENSE E TRICHODERMA HARZIANUM NO CULTIVO DE AMENDOIM - Alves Gottardi, Guilherme; Alves Gottardi, Gabriel; Gabriel de Souza Ricardo , Victor; Anacleto Alves da Silva , Matheus; Gabriel Alves Bonfim , Willian; Zoz, Tiago (ANAIS DO ENIC, 2026)
-